2011
DOI: 10.1111/j.1551-2916.2011.04827.x
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Oxide Nanoparticles Precipitated from Low‐Temperature Aqueous Solutions: III. Thin Film Properties

Abstract: In our previous reports (Part I and II), we have identified precursor “supersaturation” as a key parameter to control the precipitation behavior of titania nanoparticles in a temperature‐driven hydrolysis process from the chemical bath of soluble titanium salt. Through this protocol, a methodology was developed to grow titania films with controlled microstructures and phases. In this study, we deposited titania films containing anatase or rutile as a dominant phase along with microstructures of various film de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…3 Being able to tailor this mesostructure would help improving the strength, functionality, and durability of important engineering materials, such as mesoporous metal oxides, zeolites, and cement paste. 4,5 The current approaches to mesostructural optimization are mostly empirical [6][7][8] . What is missing is a theoretical understanding of the relationship between mechanisms of nanoparticle precipitation/aggregation and experimental synthesis variables, such as solution chemistry and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…3 Being able to tailor this mesostructure would help improving the strength, functionality, and durability of important engineering materials, such as mesoporous metal oxides, zeolites, and cement paste. 4,5 The current approaches to mesostructural optimization are mostly empirical [6][7][8] . What is missing is a theoretical understanding of the relationship between mechanisms of nanoparticle precipitation/aggregation and experimental synthesis variables, such as solution chemistry and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, chemical potential, and the number of moles, or equivalently the chemical activities of the reactants, and products can play a signicant role in the phase, and shape of the deposited TiO 2 lms. Roy et al 25 have studied not only the deposition conditions but also the properties of TiO 2 thin lms produced by solution bath deposition method. This can be translated as another term in eqn (1).…”
Section: Introductionmentioning
confidence: 99%
“…After hydrolysis reaction of TiCl 4 in aqueous solution, Ti ion can exist in a basic monomeric [Ti(O)(H 2 O) 5 ] 2+ form and this sixfold coordinated structure becomes octahedrons after the condensation reactions. The formation of crystalline phase would then be governed by pH . At lower supersaturation (i.e., lower pH) during the solution process, the condensation reaction would be hindered by a repulsion force from the adsorbed H + ions so the precipitation should occur slowly and the rutile structure can be attained.…”
Section: Resultsmentioning
confidence: 99%
“…There are three common types of crystalline phases (rutile, anatase, and brookite), each of which shows unique properties. Especially rutile is thermodynamically the most stable phase compared to the other two polymorphs, often being considered for electrical and optical ceramic materials . On the other hand, the anatase phase is thermodynamically metastable at ambient conditions and has been reported that it exerts higher performance as a photocatalytic material and gets even better when mixed with a rutile structure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation